Implementation of an Integrated Organic Farming System to Empower Local Farmer Groups in the Highlands of Bali - Wang Junn; Zhang Li; Putu Fajar Kartika Lestari; Miko Purnomo (Yayasan Adra Karima Hubbi, 2025)
Background. Agricultural sustainability in Bali’s highland regions faces increasing challenges due to soil degradation, excessive chemical input, and the decline of traditional farming practices. These issues threaten both environmental resilience and the socio-economic stability of smallholder farmers. Purpose. This study aims to implement and evaluate an integrated organic farming system designed to empower local farmer groups through environmentally sustainable and economically viable agricultural practices. Method. The research employed a participatory action research (PAR) method involving 60 farmers across three highland villages Kintamani, Pelaga, and Pupuan. The program integrated organic composting, biopesticide application, crop rotation, and market linkage training. Data were collected through field observations, yield measurements, and pre- and post-intervention surveys assessing knowledge, productivity, and income. Results. Results of the study demonstrated that the implementation of an integrated organic farming system effectively improved agricultural productivity, environmental quality, and farmers’ socio-economic well-being in the highlands of Bali. Conclusion. The study concludes that implementing a community-based organic farming model can simultaneously promote environmental restoration and rural economic empowerment. The success of this approach demonstrates its potential scalability for sustainable agriculture programs across Indonesia’s highland ecosystems.